2020
DOI: 10.3389/fcell.2020.548605
|View full text |Cite
|
Sign up to set email alerts
|

Histone Demethylase JMJD3 Mediated Doxorubicin-Induced Cardiomyopathy by Suppressing SESN2 Expression

Abstract: Jumonji domain-containing 3 (JMJD3) protein, a histone demethylase protein, specifically catalyzes the demethylation of H3K27 (H3K27me3) and regulates gene expression. Sestrin2 (SESN2), a stress-inducible protein, protected against doxorubicin (DOX)-induced cardiomyopathy by regulating mitophagy and mitochondrial function. Here, the expression of JMJD3 was increased and that of SESN2 was decreased in both the heart samples from patients with dilated cardiomyopathy and chronic DOXstimulation induced cardiomyopa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 52 publications
0
16
0
Order By: Relevance
“…14 For example, JMJD3 reduced H3K27me3 in the promoter region of sestrin2, and knockdown of JMJD3 ameliorated doxorubicin-induced cardiomyopathy. 15 JMJD3 also demethylated H3K27me3 at the promoter of β-MHC, and inhibition of JMJD3 attenuated isoproterenol-induced cardiac hypertrophy through suppression of β-MHC. 16 Therefore, lysine methylation of histones regulated by JMJDs was associated with cardiovascular diseases.…”
Section: Discussionmentioning
confidence: 96%
“…14 For example, JMJD3 reduced H3K27me3 in the promoter region of sestrin2, and knockdown of JMJD3 ameliorated doxorubicin-induced cardiomyopathy. 15 JMJD3 also demethylated H3K27me3 at the promoter of β-MHC, and inhibition of JMJD3 attenuated isoproterenol-induced cardiac hypertrophy through suppression of β-MHC. 16 Therefore, lysine methylation of histones regulated by JMJDs was associated with cardiovascular diseases.…”
Section: Discussionmentioning
confidence: 96%
“…Studies have confirmed that Dox is transformed into highly oxidative metabolites in mitochondria and induces redox imequilibrium [ 52 ]. There are many reports that mitochondrial mediated DIC causes apoptosis, and mitochondria have also become crucial targets for possible intervention [ [73] , [74] , [75] , [76] ]. Our previous studies have found that some phytochemicals upregulated 14-3-3γ expression, phosphorylated Bad, promoted the migration of Bcl-2 to mitochondria, reduced mPTP openness, inhibited apoptosis of cardiomyocytes and vascular endothelial cells, and resisted Dox toxic injury [ [12] , [13] , [14] , [15] ].…”
Section: Discussionmentioning
confidence: 99%
“…Histone modification affects many cellular pathways essential for the normal function and development of the heart and blood vessels (110,(118)(119)(120). The methyltransferase SET7 induces the upregulation of NF-κB p65 as a result of enhanced monomethylation of H3K4 in aortic ECs (121).…”
Section: Histone Methylation-mediated Cellular Functions and Pathways In Cvdsmentioning
confidence: 99%